DEVELOPING AND MEASURING ATTENTION IN BOXERS: MIXED COACHES’ EXPERTISE AND REACTION TIME MEASURES - Kolesovs, Aleksandrs; Salkovs, Deniss; Blinovs, Aleksejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
This study explored the problem of attention and its development in young boxers. A rapidly changing situation and a high level of traumatization in boxing are demanding the development of athletes’ attention. Focusing on technical or motivational training is among the reasons for underestimating the development of attentional skills. Study 1 involved seven expert coaches (males, mean age 45.4, mean working experience 20.3 years). The results revealed a relatively high assessment of the psychological component of training and a low agreement on the development of attentional skills. Coaches indicated that testing is the best measurement of attention. Study 2 focused on the measurement of reaction time (RT) in young boxers. Simple and complex RT of nine athletes, aged 12 to 15 (33% females), were assessed before and after the 15 minutes long warm-up. The results demonstrated no significant change in boxers' simple RT and a decrease (about 30 ms) in complex RT after the warm-up. The feedback was provided for athletes and their coaches. A contrast appeared between coaches’ view of well-known exercises for developing attention and their question “Could you suggest some exercise?” Simultaneously, coaches suggested a more specific RT measurement, including the full time of a punch.